Bye, baby : a novel - Lovering, Carola (St. Martin's Press, 2024)
"Best friends don't always have the best intentions. On a brisk fall night in a New York apartment, 35-year-old Billie West hears terrified screams. It's her lifelong best friend Cassie Barnwell, one floor above, and she's just realized her infant daughter has gone missing. Billie is shaken as she looks down into her own arms to see the baby, remembering - with a jolt of fear - that she is responsible for the kidnapping that has instantly shattered Cassie's world. Once fiercely bonded by their secrets, Cassie and Billie have drifted apart in adulthood, no longer the inseparable pair they used to be in their small Hudson Valley hometown. Cassie is married to a wealthy man, has recently become a mother, and is building a following as a lifestyle influencer. She is desperate to leave her past behind - including Billie, who is single and childless, and no longer fits into her world. But Billie knows the worst thing Cassie has ever done, and she will do anything to restore their friendship... Told in alternating perspectives in Lovering's signature suspenseful style, Bye, Baby confronts the myriad ways friendships change and evolve over time, the lingering echoes of childhood trauma, and the impact of women's choices on their lifelong relationships"--